The Role of Spiritual-Based Leadership as Predictor in Improving Employee Performance - Hidayah, Siti; Sutopo, Sutopo (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2017)
This study aims to develop the concept of spiritual-based leadership in solving the controversy of empirical research results. This leadership relies more on spiritual intelligence in its leadership activities, and maintains ethical values and divine values. The population is all employees who come from 13 Baitul Mal Wa Tamwil (BMT) in Semarang City. Samples is set at 100 people as respondents. The sample that is feasible to process is 79 samples. While the sampling technique is stratified sampling technique, then each sample is selected using random sampling. Testing of hypothesis is using linear regression analysis method with program SPSS Version 16.0. The results showed that the spiritual-based leadership has positive and significant effect on the em-ployee performance at BMT in Semarang City proved acceptable. This means that spiritual-based leadership can be said to have a role as a predictor in improving employee performance. For the next, The reseach can develope to improve performance by another variable. The vari-able like another leadership style and spiritual motivation.